(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Components of mixtures have to be in required proportion and homogeneous mixed to provide good quality of briquettes or pellets. Analyzing the mixing processes several advantages for mixing biomass with an in-flow or continuous mixer was discovered. To provide better quality of in-flow mixing process an electrical charge can be applied to the particles using corona discharge. When a sharply pointed electrode is raised to a high potential, the intense electrical field at its tip ionizes the air in its immediate vicinity. To mix particles of different bulk materials, it is necessary to give a negative electrical charge to one material, and a positive electrical charge to other material particles. The electrical charge provides mixing on a small scale, and electrostatic forces drive the process towards a perfect mixture. In this article experiments of in-flow mixer equipped with electrodes of corona discharge is described. Three different rotation frequencies (20, 35 and 50 rpm) of conveyer shaft and five different voltages (0, 5, 10, 15, 20 kV) of corona electrodes were used to evaluate impact on flow direction of balk material.